Assessment of spread foundation settlement using statistical determination of characteristic values of subsoil properties - Rabarijoely Simon; Lechowicz Zbigniew; Sulewska Maria Jolanta (Studia Geotechnica et Mechanica)
According to Eurocode 7, limit state design codes generally draw more attention to ultimate limit states than to serviceability limit states. This paper presents the problem of settlement assessment of spread foundations on clays when the foundation design is governed by the serviceability limit state requirements. The paper presents the test results of geotechnical parameters for heavily preconsolidated boulder clays (sandy clay saCl and silty sandy clay sasiCl), which prevail on the Warsaw University of Life Sciences – SGGW campus. The test results were used for settlement calculations of spread foundations. Based on the results of field and laboratory tests, the problem of spatial variability assessment and determination of the characteristic value of soil parameters was addressed. Classical statistics and Bayesian analysis were used in the statistical analysis of the test results. Settlements of spread foundations were calculated based on the soil parameters obtained from cone penetration tests (CPTs) and dilatometer tests (DMTs). Special attention was drawn to the selection of the characteristic values of soil parameters. Determination of the characteristic value of the constrained modulus Mk was performed using two methods: according to the well-known and frequently used formula proposed by Schneider (1997; 1999) and according to the European draft standard prEN 1997-1:2022-09. Settlement calculations of spread foundations were carried out taking into account changes in the stresses and the constrained modulus in the subsoil. The calculated settlements were verified by field measurements performed during the construction of the object. Comparison of settlements obtained from the characteristic values of the constrained modulus Mk estimated according to prEN 1997-1:2022-09 with the measured settlements indicates that the calculated values were significantly higher than the measured values. Smaller differences between the measured and calculated settlements were obtained when the characteristic values of the constrained modulus Mk were determined from Schneider's formula, while smaller differences were obtained when the mean values of the constrained modulus Mmean were used.